Mental, physical, environmental, and financial challenges of students: do challenges and demographic profile affect students' perceived hope? - Jomar Aban; Aisha N Sevilleja; Jenilyn A. Asirot; Rachelle D. Ebueza; Sheila E. Calica; Mayeth G. Navasca (Universidade Estadual de Alagoas, 2024)
Studying in a university is one of the most difficult stages in an individual's professional and personal development. During this stage, the individual experiences myriads of challenges including environmental challenges, financial constraints, mental problems and physical stress.  The study is conducted to determine the physical, mental, financial and environmental challenges by the students in the University. The population of the study were 1,199 students' university students at a higher education institution from the Philippines. The demographic profile questionnaire was initially utilized. After which, the respondents were asked to identify their challenges using a researcher-developed survey questionnaire. The hopelessness questionnaire used in the study was extracted from a standardized compendium of assessment tools. The respondents' profiles show that the majority were female and were not beneficiaries of the Pantawid Pamilyang Pilipino Program (4Ps). Majority were full time students and many of them came from a family with monthly income less than P12,082.00. Students were found to have high levels of physical challenges and exhaustion at school, were moderately mentally challenged, and have moderate level of financial and environmental challenges. They have a moderate level of financial challenges and moderate level of environmental challenges. Kendall's Tau-B indicated no relationship between the profile of the respondents and the challenges they experienced. Students profile (p-value) in terms of sex, 4Ps, employment status and monthly financial income, respectively for the following challenges experienced: Physical= 0.239; 0.749; 0.462; 0.992, respectively; Mental= 0.878; 0.800; 0.680; 0.576, respectively; Financial= 0.519; 0.323; 0.166; 0.067, respectively; and Environmental = 0.776; 0.492; 0.661; 0.449, respectively. The results of the hopelessness questionnaire indicate that the majority of the students manifested a moderate level of hopelessness. It can be concluded that the physical, mental, environmental and financial challenges of students experienced by students have no relationship with their sociodemographic status but these challenges moderately affected their hope. The data on this present study suggested a need for an intervention to facilitate the struggles of the students in the academe and help them strive to finish their chosen degree.